Bilirubin Down-Regulates Oxidative Stress and Fibroblast Growth Factor 23 Expression in UMR106 Osteoblast-Like Cells - Rausch, Steffen; Hammerschmidt, Katharina; Feger, Martina; Vítek, Libor; Föller, Michael (Experimental and Clinical Endocrinology & Diabetes, 2024)
Introduction Fibroblast growth factor 23 (FGF23) is a major regulator of phosphate and vitamin D metabolism in the kidney, and its higher levels in plasma are associated with poorer outcomes in kidney and cardiovascular diseases. It is produced by bone cells upon enhanced oxidative stress and inhibits renal phosphate reabsorption and calcitriol (active form of vitamin D) production. Bilirubin, the final product of the heme catabolic pathway in the vascular bed, has versatile biological functions, including antioxidant and anti-inflammatory effects. This study explored whether bilirubin alters FGF23 production.Methods Experiments were performed using UMR106 osteoblast-like cells. Fgf23 transcript levels were determined by quantitative real-time polymerase chain reaction, C-terminal and intact FGF23 protein levels were determined by enzyme-linked immunosorbent assay, and cellular oxidative stress was assessed by CellROX assay.Results Unconjugated bilirubin down-regulated Fgf23 gene transcription and FGF23 protein abundance; these effects were paralleled by lower cellular oxidative stress levels. Also, conjugated bilirubin reduced Fgf23 mRNA abundance.Conclusion Bilirubin down-regulates FGF23 production in UMR106 cells, an effect likely to be dependent on the reduction of cellular oxidative stress.
Keywords: Klotho; ROS; phosphate